Generic analysis metamodel based on service oriented software design - Nik Daud, Nik Marsyahariani (Asian Research Publishing Network (ARPN), 2015)
Analyzing software in order to evaluate its quality attributes is not a foreign concept in software lifecycle. There are many methods that can be implemented to analyze software with some focusing on source code analysis and others concentrating on analyzing software artifacts from various phases such as design artifacts. Service oriented software is not excluded from this. As software that uses services as part of its functionalities, service oriented software designs represent more completed view of the software compared to other artifacts. This work focus on identifying elements from design artifacts that represent service oriented software structure and behavior based on standard modeling language for service oriented architecture. The elements are then represented in a generic metamodel that can be used to analyze the software. A case study will be used to show how design artifacts from selected standard modeling language, SoaML being mapped to model based on proposed metamodel